THE STRUCTURE OF PARAMYOSIN FIBRILS ACCORDING TO X-RAY DIFFRACTION - Bear, Richard S. (The Rockefeller University Press, 1956)
From analysis of x-ray diffraction patterns obtained with improved small-angle techniques has been derived the following description for the structure of the fibrils of the fibrous protein, paramyosin, obtained in this case from "white" portions of the adductor muscle of the clam, Venus mercenaria: 1. About 25 significantly different diffraction maxima have been resolved and found accounted for as (hk) reflections of a net whose cell elements are, for the dry material: a = 250 A, b = 720 A (fibril axis identity period), and γ = 90.5° (angle included between a and b axes). For rehydrated material a is larger (ca. 325 A), b is essentially unchanged, and γ is slightly larger. There remains an unresolved discrepancy between the electron-optically derived, cell's a dimension (193 A) and that here reported for dry samples. 2. The h = ±1 row lines are crossed on the diagrams (because γ is not 90°) and thus can be distinguished in spite of natural "rotation" of fibrils (within the massive fibrous specimens) about their commonly oriented axes. The observed reflections are then found to obey a selection rule which indicates that the net cell is non-primitive and contains 5 equivalent locations (nodes) arranged as shown in Fig. 5. The nodal distribution is the same as has been previously photographed electron-optically. 3. Analysis of reflection lengths indicates that the native fibrils are not noticeably ribbon-like, having dimensions normal to the ordered net layers approximating their width across the fibril in the plane of the net layers. Corresponding transverse, interlayer spacings (possibly ca. 100 A) have not been observed, however, and may be hidden in troublesome central scatter. 4. Since paramyosin's wide-angle diffraction is very probably of α-type, supercoiled α-helices must be involved according to current interpretations of α-diagrams. Physicochemical evidence suggests that cables of this type, ca. 1400 A in length, may extend over two cells. Of two possible nodal connections, a favored one is shown in Fig. 5 to join 5 nodes in this way. Considerations of space filling, of transverse distribution of small-angle x-ray scattering, and of nodal significance, suggest that the cable units may be further aggregated into supercables, essentially forming rather solid rods of ca. 100 A diameter. 5. An alternative interpretation of the paramyosin small-angle diffraction, in particular of the observed selection rule, would conclude that large particles are arranged in a helical way, with minimum helix diameter about 150 A (dry). The simplest (genetic) particle connection would have 5 particles in 2 coil turns along 720 A of fibril or helix axis. This view is distinctly different from the arrangement of "rods" in net-like layers as given above, even though the rods are said to be made of supercoils or cables. Reasons are given for preferring the net-of-rods explanation over the particulate-helix model. The helix- vs. true-net ambiguity arises whenever the two types of structure are conceivable, and decision between them is difficult on the basis of the diffraction data alone.